GULJAMOL ASQAROVA’S PLACE IN THE KATTAKURGON LITERARY ENVIRONMENT - Azimova Dilobar (Next Scientists Conferences, 2025)
The article reveals the specific features of the existing literary environments in our literary studies through in-depth study and analysis. A thorough analysis and understanding of one of these literary environments, the literary environment of Kattakurgan, is one of the most important tasks in our literary studies today. The spirit of Guljamol Askarova’s poems, the skill of using words, and the units of reference were scientifically examined in our research. Also, the article analyzes the units in Guljamol Askarova's poems “Ojizlik” and “Umid” as objects of pragmalinguistics.